2017
DOI: 10.1055/s-0043-102510
|View full text |Cite
|
Sign up to set email alerts
|

Four New Xanthones from Cratoxylum cochinchinense and Their In Vitro Antiproliferative Effects

Abstract: The study of the chemical constituents of branches and twigs of collected in Singapore led to the isolation and structural elucidation of four new xanthones, named cratoxanthone A (), B (), C (), and D (), together with six known xanthones (-) and one known dihydroanthracenone (). Eight xanthones (including and) and were tested for their antiproliferative activity in three human carcinoma cell lines (lung adenocarcinoma A549, colorectal carcinoma Colo205, and epidermoid carcinoma KB) and a human acute lymphobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…NALM‐6 cells were seeded into 96‐well plates at 1 × 10 5 cells per well. After the cells were incubated for 24 h, they were treated with 20 μ m acrofolione A ( 1 ) or B ( 2 ) and cultured for 48 h. The mitochondrial membrane potential of the cells was measured using a membrane potential cytotoxicity kit (Mito‐ID; Enzo Life Science International, Plymouth Meeting, PA, USA) according to the manufacturer's instructions . Briefly, mitochondrial membrane potential solution was applied to each treated cell sample and incubated for 30 min at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…NALM‐6 cells were seeded into 96‐well plates at 1 × 10 5 cells per well. After the cells were incubated for 24 h, they were treated with 20 μ m acrofolione A ( 1 ) or B ( 2 ) and cultured for 48 h. The mitochondrial membrane potential of the cells was measured using a membrane potential cytotoxicity kit (Mito‐ID; Enzo Life Science International, Plymouth Meeting, PA, USA) according to the manufacturer's instructions . Briefly, mitochondrial membrane potential solution was applied to each treated cell sample and incubated for 30 min at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…After the cells were incubated for 24 h, they were treated with 20 lM acrofolione A (1) or B (2) and cultured for 48 h. The mitochondrial membrane potential of the cells was measured using a membrane potential cytotoxicity kit (Mito-ID; Enzo Life Science International, Plymouth Meeting, PA, USA) according to the manufacturer's instructions. [4] Briefly, mitochondrial membrane potential solution was applied to each treated cell sample and incubated for 30 min at 37°C. After washing with HBSS buffer, the fluorescence intensity of the treated cells was measured at 490 nm excitation and 590 nm emission using the FACS Canto II flow cytometer.…”
Section: Annexin V/propidium Iodide Stainingmentioning
confidence: 99%
See 1 more Smart Citation
“…As a deciduous shrub or tree, Cratoxylum cochinchinense belongs to the Clusiaceae plant family, in which some species have been used historically as traditional medicines ( Duan et al, 2012 ). Previous phytochemical investigations have indicated that the plants of Cratoxylum genus are rich in xanthones with extensive biological activities including anti-malaria, anti-bacteria, anti-HIV, and cytotoxicity ( Laphookhieo et al, 2006 ; Laphookhieo et al, 2009 ; Rattanaburi et al, 2014 ; Duan et al, 2015 ; Ito et al, 2017 ; Li et al, 2018 ; Huang et al, 2019 ; Jia et al, 2019 ; Lv et al, 2019 ). Some xanthones, e.g., gambogic acid, were found to have promising cytotoxic effects and be potentially useful for the discovery of anticancer lead compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Cratoxylum cochinchinense Blume (Clusiaceae) is a deciduous shrub tree growing abundantly in southeast Asian countries [1]. The leaves, stems, barks, roots and latex of C. cochinchinense have been used as traditional Chinese medicine for the treatment of various diseases such as jaundice, edema, cough, itch, fever, diarrhea, hoarseness, diuretic, flu, colic, ulcer and dental problems and so on [24]. In addition, the young leaves have been used as an herbal substitute for tea and the immature fruit as a spice for cooking [5].…”
Section: Introductionmentioning
confidence: 99%